LAE-LAE SEBAGAI DESTINASI WISATA ARKEOLOGI DI MAKASSAR, INDONESIA - Yusriana Yusriana; Rosmawati Rosmawati; Khadijah thahir Muda (Universitas Merdeka Malang, 2019)
Lae-Lae Island is a small island to the west of Makassar City which is one of the marine tourism destinations. The findings of archaeological remains on the island indicate that the island of Lae-Lae has a new attraction that is different from what is currently and can be developed towards archaeo-tourism. This article intends to describe the potential of archaeology in Lae-Lae Island. The method used consist of observation, documentation, and interview, and descriptive analytic approach. Interviews were conducted with island residents, the government in this case the local government and the preservation of cultural heritage in South Sulawesi. The results of this study explain that based on the four basic aspects of tourism products are Attractions, Accessibility, Amenities, and Institutional that Lae-Lae Island has the object attraction of two Japanese bunkers and an old well built since World War II in the Straits Makassar. In addition, the attraction of archaeological findings at the bottom of the Makassar Strait waters can also be developed into a special interest tourism package. However, currently these remains have not received the government's attention in terms of conservation so that it becomes an input for the government to immediately preserve because the finding conditions, especially the bunkers, are currently still concerning. The accessibility to Lae-Lae Island is quite adequate even though of course it needs better improvements. The facilitation aspects need to add adequate facilities, especially homestays that are in accordance with the standards and need guidance on culinary potential on the island that can support the running of tourism activities. The ancillary aspect is very much needed to support and foster the government to establish an institutional system of island communities in the management of tourist objects, especially those archaeological objects.